The social and solidarity economy as tools for strengthening training in entrepreneurship with a rural approach - Jurado Paz, Irina Margarita; Riascos Mora, Amanda Janneth (SATHIRI, 2020)
The concepts of social and solidarity economy, as well as other new trends that favor a less aggressive capitalist economy are theoretically very rich, which can be incorporated into training in rural entrepreneurship so that it is possible to involve more relevant elements for the communities, recognizing their cultural, social and environmental riches. In the following document, based on a documentary systematization, a reflection was built on how it is possible to articulate the social and solidarity economy, the collaborative economy, inclusive businesses and green businesses in the formation of rural entrepreneurship, so that in turn this is more contributing to the strengthening of the territories. The methodology used for the construction of this writing was the documentary search, subsequently a review of the material was made and the one that would meet quality criteria was selected (established by the year of publication, the scientific criteria of the source publication and the relationship with the research topic), once this classification was made, it was processed in specialized software for this purpose and the results of which allow us to make this reflection. The main conclusion of this reflection is centered on the importance of building entrepreneurial training methodologies that incorporate more social, supportive, cooperative, collaborative and environmentally-friendly concepts, in addition to facilitating the social appropriation of the ancestral knowledge of peasant and rural communities. indigenous people, who at various times in history have developed successful entrepreneurship models based on these criteria.
Keywords: Training in rural entrepreneurship; social and solidarity economy; rural entrepreneurship